Zygophylax levinseni ... - Peña Cantero, Álvaro L.; Horton, Tammy (Zenodo, 2017)
Zygophylax levinseni (Saemundsson, 1911) (Fig. 5C–H) Lictorella levinseni Saemundsson, 1911: 86, fig. 2. Zygophylax biarmata — Broch, 1918: 24; Kramp, 1938: 28 [not Zygophylax biarmata Billard, 1905] Zygophylax elegantula Leloup, 1940: 11, pl. 1 fig. 8; Rees & Vervoort, 1987: 78; Zygophylax levinseni — Ramil & Vervoort, 1992: 78, figs 18a–d, 19a–f; Altuna Prados & Álvarez Claudio, 1994: 6–10, figs 3, 4; Calder & Vervoort, 1998: 35, fig. 17a–c; Schuchert, 2001: 71–72. Zygophylax sp. Aguirrezabalaga et al., 1988: 119, figs 12a–f. Not Zygophylax levinseni — Calder & Vervoort, 1998: 35, fig. 17a–c. Material examined. 9752#1, several stems up to 60 mm high, on axis of dead gorgonian and S. plicatile, with coppiniae; 13881#1, several stems up to 11 mm high, on Sertularella gayi, no coppiniae. Description. Polysiphonic stems, up to 60 mm high. Polysiphony extending almost to end of stem. Primary branches also polysiphonic. Branching alternate in more or less one plane and roughly at right angle ... : Published as part of Peña Cantero, Álvaro L. & Horton, Tammy, 2017, Benthic hydroids (Cnidaria, Hydrozoa) from bathyal and abyssal depths of the Northeast Atlantic held in the modern Discovery Collections, pp. 1-30 in Zootaxa 4347 (1) on pages 13-14, DOI: 10.11646/zootaxa.4347.1.1, http://zenodo.org/record/1044772 ...